Application of zinc oxide nanoparticles and sodium chloride in bell pepper - Magdaleno-García, Guadalupe; Juárez-Maldonado, Antonio; Betancourt-Galindo, Rebeca; González-Morales , Susana; Sánchez-Vega, Miriam; Cabrera-De la Fuente, Marcelino; Méndez-López, Alonso (Ecosistemas y Recursos Agropecuarios, 2024)
Zinc oxide nanoparticles (ZnO NPs) have attracted a lot of attention due to their beneficial properties and because they can be applied in agriculture as nanofertilizers, nanogrowth regulators and to improve quality parameters. The use of eustressors such as sodium chloride (NaCl) can improve the quality of various vegetable crops with special interest in fruit quality attributes. The objective of this research was to evaluate the effects of NaCl as eustress and ZnO NPs on the growth and quality of chili pepper. 10 treatments were evaluated: application of NPs of spherical and hexagonal morphology in doses of 50 and 100 mg L−1 with and without application of NaCl (50 mM), plus saline control and absolute control. In the study, agronomic variables were evaluated plant height (AP), stem diameter (DT), root dry weight (PSR) and plant (PSP), fruit weight per plant (PFP) and fruit quality variables. fruit as: firmness, pH, electrical conductivity (EC), total soluble solids (TSS), titratable acidity (AT), oxidation-reduction potential (ORP) and vitamin C. The results obtained show that the treatments with nanoparticles at 50 and 100 mg L−1 increased the parameters of AP, PSR, PSP and PFP, hexagonal morphology improved AP, PSR and PSP, the combination of NaCl plus NPs increased PSP NaCl improved firmness and ORP, NPs were favorable for quality, although spherical and hexagonal shapes produced similar effects.